2015
DOI: 10.1111/eos.12234
|View full text |Cite
|
Sign up to set email alerts
|

Fixed orthodontic appliances cause pain and disturbance in somatosensory function

Abstract: This study aimed to assess the short-term effects of orthodontic pain on quantitative sensory testing (QST) in subjects receiving fixed orthodontic treatment. Twenty patients and 12 healthy volunteers (as controls) participated. All 20 patients had bonded AO self-ligating brackets, with a 0.014 super elastic nickel-titanium arch wire placed in the brackets. Pain [self-reported on a visual analog scale (VAS)], and thermal and mechanical thresholds, were tested at six time points--before (baseline), and 2 h, 24 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 37 publications
1
18
2
1
Order By: Relevance
“…Shen et al. found a hypersensitive to cold and hyposensitive to pressure at the site of the tooth movement up to 1 month after orthodontic force was applied . Both studies found some somatosensory alteration intraorally which diverge from the extraoral examination of the present investigation.…”
Section: Discussioncontrasting
confidence: 41%
See 4 more Smart Citations
“…Shen et al. found a hypersensitive to cold and hyposensitive to pressure at the site of the tooth movement up to 1 month after orthodontic force was applied . Both studies found some somatosensory alteration intraorally which diverge from the extraoral examination of the present investigation.…”
Section: Discussioncontrasting
confidence: 41%
“…In contrast to previous investigations, which applied either elastic separator around the first molars or fixed orthodontic appliance to induce pain, we examined both methods of stimulating orthodontic tooth movement. Patients reported a moderate pain intensity 24 hour‐aBB and only mild pain intensity following elastomeric separator which was expected since the separator only stimulate two contiguous teeth in contrast to fixed appliance which stimulates all teeth on the arch.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations